How can data analytics and employee upskilling foster digital maturity and sustainable practices in SMES? - Levente Peter Balint; Adam Pentek; Zsofia Nabradi; Szilvia Botos (Problems and Perspectives in Management)
The accelerating pace of digital and environmental transformation presents both opportunities and challenges for small- and medium-sized enterprises (SMEs) across the European Union. While digital tools like data analytics can significantly boost operational efficiency and sustainability, many SMEs lack the internal capabilities to fully leverage them. This study investigates how upskilling employees in digital competencies can help SMEs enhance their digital maturity and achieve long-term resilience. A descriptive trend analysis was based on Eurostat datasets focusing on enterprise size categories and examining indicators such as data analytics activities, the prevalence of ICT training, and difficulties encountered in recruiting ICT specialists. Visualized through Tableau, the data reveal notable disparities: in 2023, only 14.5% of small and 33.8% of medium-sized enterprises with high digital maturity performed data analytics, compared to 59.4% of large enterprises. Despite clear demand, only 5% of small and 20% of medium enterprises attempted to recruit ICT-skilled personnel, frequently citing a lack of qualified candidates or unaffordable salary expectations. SMEs rely on their own staff for data analytics tasks, yet many still do not offer structured training. While countries like Finland stand out, with 61.7% of medium enterprises providing ICT upskilling, others fall well below the EU average. These results underscore that internal skill development is not just a workaround but a strategic necessity for SMEs striving to keep pace with digital demands, overcome labor market constraints, and build a foundation for sustainable growth.